Talent Measurement Model of Islamic Banking: Theoretical and Practice Perspectives - Samidi, Sudarmawan (Sekolah Tinggi Manajemen IPMI, 2024)
Talent measurement is a crucial component of talent management (TM). It involves the application of various measurement methodologies to assess the current and long-term potential, competencies, and contributions of employees in their roles. This study explores and integrates the theory of talent measurement from previous research with the practice of talent measurement model in Islamic banking. This study uses personal interview with the experts from selected Islamic banking in Indonesia, provides insights into how the traditional nine-box grid model is adapted within the context of Islamic banking, incorporating the principles of Maqāṣid al-Sharīʿah to ensure alignment with Islamic values. The findings suggest that integrating ethical dimensions into talent evaluation enhances fairness, employee engagement, and long-term organizational sustainability. Furthermore, the study highlights the importance of addressing talent risk factors and suggest strategies to improve talent retention in Islamic banking. This research offers valuable contribution to both theory and practice, proposing a more holistic and values-driven approach to talent management in the Islamic financial sector.